Equity Valuation of Cimpor - Algarvio, David Nuno Prazeres (2013)
Based on the major theme of Equity Valuation, this thesis has as its main purpose the valuation of Cimpor, the biggest Portuguese cement producer and one of the largest in the World. In order to achieve the final value of such company, a detailed research work had to be done regarding all the possible valuation methods that could be used, which involved a rigorous study over the entire Equity Valuation theory. By reviewing all the available valuation methods and afterwards studying the company structure and organization, the methodology was chosen and followed according to the parameters established by the explained theory. This process led to a final value for the company that was not only discussed by itself, but also compared with the value achieved by a valuation elaborated by the Equity Research team of BES Investimento. According to the methodology followed, the assumptions made and the comparison with the results from the referred investment bank, the final conclusions were expressed.